Prevention and Management of Government Arrears - Flynn, Suzanne (Technical Notes and Manuals; Technical Notes and Manuals ;, 2014)
The accumulation of government expenditure arrears is one of the most common problems in public financial management. This technical note defines expenditure arrears and the different types of arrears that arise. The economic impact of chronic expenditure arrears accumulation is highlighted. The note discusses the underlying causes and mechanisms for preventing and controlling the further accumulation of arrears. The note concludes with some strategies for managing and clearing arrears.